Policing homicide in urban and rural areas - Lawshe, Nathaniel L. (Routledge handbook of homicide studies, 2024)
This chapter synthesizes the research on policing homicide in urban and rural areas. We first discuss resident homicide in urban and rural areas. Second, we consider differences in law enforcement agency culture and structure across urban and rural areas. Third, we compare police behavior in urban and rural areas, focusing on police use of force and officer-involved shootings. Fourth, we contemplate differences in police victimization across urban and rural areas. Finally, we consider how differences in resident homicide, law enforcement agencies, police behavior, and police victimization should move police reform forward. Overall, rural police agencies are smaller, flatter hierarchically, less specialized, and more connected to community residents than urban police agencies. These differences affect the nature of police-resident interactions and ultimately may result in differential police behavior across urban and rural areas. Police-resident encounters may be more combative in urban areas, resulting in systematic differences in how force is used across urban and rural areas.